2013
DOI: 10.1093/aob/mct090
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of photosynthesis in thin- and thick-leaved epiphytic orchids: unravelling C3–CAM plasticity in an organ-compartmented way

Abstract: Water availability modulated CAM expression in an organ-compartmented manner in both orchids studied. As distinct regions of the same orchid could perform different photosynthetic pathways and variable degrees of CAM expression depending on the water availability, more attention should be addressed to this in future studies concerning the abundance of CAM plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 59 publications
0
13
0
2
Order By: Relevance
“…Water deficit that drives closure of stomata result in reduction in CO 2 uptake and subsequent down-regulation of photosynthetic efficiency [34], which is alleviated in epiphytic orchids by carbon fixation through CAM, while achieving water economy [4] [35] [36]. Epiphytic orchids have also been reported to lose water from the leaf slowly, yet maintain high values of RWC [37].…”
Section: Discussionmentioning
confidence: 99%
“…Water deficit that drives closure of stomata result in reduction in CO 2 uptake and subsequent down-regulation of photosynthetic efficiency [34], which is alleviated in epiphytic orchids by carbon fixation through CAM, while achieving water economy [4] [35] [36]. Epiphytic orchids have also been reported to lose water from the leaf slowly, yet maintain high values of RWC [37].…”
Section: Discussionmentioning
confidence: 99%
“…While adapting to harsh habitats, some orchid species have evolved succulent storage-organs, such as pseudobulbs 8 , 9 , thick leaves 10 , and crassulacean acid metabolism (CAM) 11 , a photosynthetic pathway with high water-use efficiency 12 . Morphological and anatomical studies show that orchid plants possess desirable qualities for mitigating drought stress 10 , 13 , 14 . By measuring physiological indexes and secondary metabolites of Dendrobium moniliforme 15 , Wu et al found that increasing antioxidant enzyme activities and osmolytes play an important role in protecting plants under drought stress.…”
Section: Background and Summarymentioning
confidence: 99%
“…In addition to distinctive metabolic and physiological features, CAM species typically possess anatomical traits such as thickened, succulent leaves or stems (Borland et al, 2018). Succulence facilitates the vacuolar storage of malic acid as well as water (Balsamo and Uribe, 1988;Rodrigues et al, 2013), and enhances CO 2 trapping during the daytime decarboxylation of CAM by reducing the intercellular air space of the leaf (Borland et al, 2018). Such anatomical characteristics are likely to impose specialized roles for proteins implicated in the transport of CO 2 and water within the mesophyll and epidermis.…”
Section: Introductionmentioning
confidence: 99%